Location of the BCR/ABL Fusion Genes on Both Chromosomes 9 in Ph Negative Young CML Patients: An Indian Experience - Brahmbhatt, Manisha M. (Indian J Hematol Blood Transfus, 2014)
The BCR/ABL gene rearrangement is cytogenetically visualized in most chronic myeloid leukemia (CML) cases. About 5–10 % of CML patients lack its cytogenetic evidence, however, shows BCR/ABL fusion by molecular methods. We describe two CML patients with Philadelphia (Ph) negative (−ve) and BCR/ABL positive by fluorescence in situ hybridization (FISH). Both the cases were in chronic phase at diagnosis. Conventional cytogenetics and different FISH assays were adopted using BCR/ABL probes. Home-brew FISH assay using bacterial artificial clone (BAC) for BAC-CTA/bk 299D3 for chromosomal region 22q13.31-q13.32 was performed in case 1. Both the patients were Ph-ve. In first case, dual color dual fusion (DCDF)-FISH studies revealed 1 Red (R) 2 Green (G) 1 Fusion (F) signal pattern in 80 % of cells indicating BCR/ABL fusion signals on chromosomes 9 instead of Ph and 2G2F signal pattern in 20 % of cells indicating two BCR/ABL fusions on both chromosomes 9q34 on presentation. In second case, FISH studies revealed the 1R1G1F signal pattern indicating BCR/ABL fusion signals on chromosomes 9 instead of Ph in 100 % of cells at presentation. During follow-up, both the patients exhibited 2G2F signal pattern indicating two BCR/ABL fusions on both chromosomes 9q34, which indicated a clonal evolution in 100 % cells. Both the patients did not achieve therapeutic response. Relocation of BCR/ABL fusion sequence on sites other than 22q11 represents a rare type of variant Ph, the present study highlights the hot spots involved in CML pathogenesis and signifies their implications in Ph−ve BCR/ABL positive CML. This study demonstrated the genetic heterogeneity of this subgroup of CML and strongly emphasized the role of metaphase FISH, especially in Ph−ve CML cases, as it detects variations of the classical t(9;22).